Lithium metasilicate microcrystalline glass and preparation method thereof

By adjusting the oxide composition and chemical reinforcement treatment, the problem of insufficient strength and transparency of lithium metasilicate glass is solved, and microcrystalline glass with high transparency and impact resistance is achieved to meet the needs of electronic device protection glass.

CN119143395APending Publication Date: 2024-12-17CAIHONG GRP SHAOYANG SPECIAL GLASS CO LTD +1

Patent Information

Application Number
CN202411193713.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-17
Filing Date
2024-08-28
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing lithium metasilicate microcrystalline glass has insufficient strength and transparency, which cannot meet the needs of electronic devices to protect glass covers, and its ion exchange ability and impact resistance are poor, which affects service life and safety.

Method used

By adjusting the oxide composition ratio, a lithium metasilicate microcrystalline glass was prepared, with a content of 62% to 78%, 3% to 10%, Al2O3, 4% to 18%, Li2O, 0.6% to 7.5% The values ​​of P2O5 and 2% to 15% ZrO2, (SiO2+Al2O3)/Li2O are 6 to 15, the values ​​of Al2O3/Li2O are 0.7 to 1.3, and P2O5+ZrO2 <8%, and chemical strengthening treatment is performed to form a high surface. Compressed stress and ion exchange layer to enhance the mechanical strength and transparency of the glass.

Benefits of technology

Microcrystalline glass with high transparency, strength, impact resistance and drop resistance is achieved, meeting the needs of electronic device protection glass, with large surface compressive stress and strong ion exchange capacity, and is suitable for electronic device protection materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143395A_ABST
    Figure CN119143395A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of microcrystalline glass, in particular to lithium metasilicate microcrystalline glass and a preparation method thereof, the lithium metasilicate microcrystalline glass comprises the following components in percentage by mass: 62%-78% of SiO2, 3%-10% of Al2O3, 4%-18% of Li2O, 0-5% of K2O, 0.6%-7.5% of P2O5 and 2%-15% of ZrO2, the value of (SiO2 + Al2O3) / Li2O) is 6-15, the value of Al2O3 / Li2O is 0.7-1.3, and P2O5 + ZrO2 is less than 8%. According to the technical scheme, by designing a proper basic glass material formula, a heat treatment crystallization process system and a chemical strengthening process, the high-strength transparent glass ceramic with lithium metasilicate as a main crystal phase is obtained; the glass has the characteristics of large surface compressive stress, high strength, strong ion exchange capacity, excellent impact resistance, excellent falling resistance and the like, so that the application requirement of the glass as a cover plate on an electronic product is met. The problems that in the prior art, glass ceramics are insufficient in strength and transparency and cannot meet the requirements of electronic device protection glass cover plates are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass-ceramic preparation, and in particular to a lithium metasilicate glass-ceramic and a preparation method thereof. Background Art

[0002] Lithium metasilicate glass-ceramics is a general term for a series of glass-ceramics with lithium metasilicate (Li2SiO3) as the main crystalline phase. Due to its high strength, good thermal stability and good wear resistance, lithium metasilicate glass-ceramics are widely used in the fields of medicine, electronic information, construction and machinery manufacturing, especially in the field of display device cover glass with high requirements for strength and transparency.

[0003] The main components of lithium metasilicate glass-ceramics are Li2O and SiO2. In addition, P2O5, B2O3, ZrO2, K2O, A12O3, CaO, CeO2, La2O3 and other components are added to play the role of flux, nucleating agent and the like. However, due to the influence of lithium metasilicate itself, transparent glass-ceramics containing lithium metasilicate have insufficient ion exchange capacity and too small surface compressive stress, which greatly restricts the improvement of the scratch resistance and drop resistance of the glass-ceramics cover, and further affects the service life, safety and user experience of lithium metasilicate glass-ceramics. In addition, most types of crystals in glass-ceramics easily lead to a decrease in glass transmittance, an increase in haze, and even devitrification, which limits its application as a protective material for mobile terminal equipment. Therefore, it is urgent to develop a transparent glass-ceramics with large surface compressive stress, high strength, strong ion exchange capacity, excellent impact resistance and drop resistance to meet the development requirements of electronic device protective glass. Summary of the invention

[0004] In view of the problem that the microcrystalline glass in the prior art is insufficient in strength and transparency and cannot meet the demand for protective glass cover plates of electronic devices, the present invention provides a lithium metasilicate microcrystalline glass and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a lithium metasilicate glass-ceramic, which comprises, by oxide mass percentage, 62% to 78% of SiO2, 3% to 10% of Al2O3, 4% to 18% of Li2O, 0% to 5% of K2O, 0.6% to 7.5% of P2O5 and 2% to 15% of ZrO2, the value of (SiO2+)Al2O3 / Li2O is 6 to 15, the value of Al2O3 / Li2O is 0.7 to 1.3, and P2O5+ZrO2 is less than 8%;

[0007] The microcrystalline glass includes 30% to 60% by weight of lithium metasilicate crystal phase.

[0008] Furthermore, the microcrystalline glass has a transmittance of ≥85% and a haze of ≤0.3% for wavelengths of 400 to 1000 nm under a thickness of 1 mm.

[0009] Furthermore, it also includes 0-5% ZnO, 0-3% SnO2, 0-5% Na2O, 0-5% MgO and 0-3% B2O3.

[0010] Furthermore, the glass-ceramics also includes a lithium disilicate crystal phase.

[0011] Furthermore, its Vickers hardness is greater than 800kgf / mm 2 , elastic modulus is greater than 100Gpa.

[0012] Furthermore, its fracture toughness is ≥1.0MPa·m 1 / 2 .

[0013] Furthermore, after chemical strengthening, the surface compressive stress is greater than 400 MPa, and the depth of the ion exchange layer is greater than or equal to 80 μm.

[0014] The present invention also provides a method for preparing lithium metasilicate glass-ceramics, comprising:

[0015] In terms of oxide mass percentage, 62% to 78% SiO2, 3% to 10% Al2O3, 4% to 18% Li2O, 0% to 5% K2O, 0.6% to 7.5% P2O5 and 2% to 15% ZrO2 are introduced for weighing and mixing, and heated and melted into glass liquid; wherein the value of (SiO2+)Al2O3 / Li2O is 6 to 15, the value of Al2O3 / Li2O is 0.7 to 1.3, and P2O5+ZrO2 is less than 8%;

[0016] Casting the glass liquid to obtain basic glass;

[0017] The base glass is annealed and sliced ​​to obtain sheet-shaped base glass;

[0018] The sheet-like base glass is subjected to a nucleation and crystallization heat treatment;

[0019] After the crystallization and heat treatment is completed, the sheet-like base glass is chemically strengthened to obtain lithium metasilicate microcrystalline glass.

[0020] Furthermore, the heating and melting temperature is 1500°C to 1600°C.

[0021] Furthermore, the base glass is annealed at a temperature of 400° C. to 550° C., and the annealing time is 1 to 4 hours.

[0022] Furthermore, the method of performing nucleation and crystallization heat treatment on the sheet-like base glass is as follows:

[0023] After annealing, the steel is heated to 480°C to 650°C for nucleation treatment;

[0024] After the nucleation treatment, the temperature is heated to 600°C to 900°C for crystallization treatment, and the furnace is cooled to complete the nucleation and crystallization thermal treatment.

[0025] Furthermore, the heating rate of the nucleation treatment and the crystallization heat treatment is 1°C / min to 20°C / min; the time of the nucleation treatment and the crystallization heat treatment is 0.5 to 16 hours.

[0026] Furthermore, the microcrystalline glass after crystallization and thermal treatment is chemically strengthened, the molten salt used for chemical strengthening is one or more of sodium nitrate, potassium nitrate, sodium carbonate and potassium carbonate, the strengthening temperature is 420°C to 520°C, and the strengthening time is 0.5 to 16 hours.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The lithium metasilicate glass-ceramics of the present invention comprises, by mass percentage, 62% to 78% of SiO2, 3% to 10% of Al2O3, 4% to 18% of Li2O, 1% to 5% of K2O, 0.6% to 7.5% of P2O5 and 2% to 15% of ZrO2, the value of (SiO2+Al2O3) / Li2O is 6 to 15, the value of Al2O3 / Li2O is 0.7 to 1.3, and P2O5+ZrO2 is less than 8%. Among them, SiO2 is a component for forming a network structure of glass and a component for improving chemical durability. In addition, it is also a constituent component of lithium metasilicate precipitated from lithium metasilicate glass-ceramics. In order to ensure the fusibility of the glass, the content of SiO2 is below 78%. Al2O3 is a component that increases the surface compressive stress generated by chemical strengthening and is an indispensable component for improving the strength of glass. To ensure the surface stress of lithium metasilicate glass-ceramics, the content of Al2O3 is above 3%, but the presence of Al2O3 will affect the devitrification temperature of the glass. In order to prevent the devitrification temperature of the glass from becoming too high, the content of Al2O3 should be below 10%. Li2O is a component that forms surface compressive stress through ion exchange and is a constituent component of lithium metasilicate crystals. The content of Li2O should be above 4% to ensure that the content of lithium metasilicate crystal phase produced by its combination with SiO2 is above 30% and the grain size is appropriate, ensuring the high strength and high transparency of the glass-ceramics, thereby meeting its requirements as cover glass. On the other hand, in order to ensure the stability of the glass, the content of Li2O is preferably below 18%. K2O is a component that reduces the melting temperature of glass. When there is too much K2O, the chemical strengthening characteristics are reduced or the chemical durability is reduced, so the content of K2O is preferably below 5%. ZrO2 is a component that can form a crystal nucleus during crystallization. The content of ZrO2 is more than 2%. In order to suppress devitrification during melting, the content of ZrO2 should be less than 15%. P2O5 has the effect of promoting phase separation and crystallization of glass. The content of P2O5 is preferably more than 0.6%. However, when the content of P2O5 is too much, it is easy to separate during melting. In addition, the acid resistance is significantly reduced. The content of P2O5 should be less than 7.5%. By adjusting the value of (SiO2+Al2O3) / Li2O to 6-15 and the value of Al2O3 / Li2O to 0.7-1.3, the lithium metasilicate glass-ceramics finally formed by the raw material components can be controlled to include glass phase and lithium metasilicate phase, with lithium metasilicate crystal phase as the main crystal phase, and also containing a small amount of lithium disilicate crystal phase, so that the prepared lithium metasilicate glass-ceramics has better transparency, better mechanical strength, excellent impact resistance and drop resistance, and can meet the development requirements of electronic device protective glass.

[0029] In addition, the microcrystalline glass may also include 0-5% ZnO, 0-5% Na2O, 0-5% MgO and 0-3% B2O3. ZnO can act as a flux and promote the formation and growth of microcrystalline glass while controlling the size of the crystal material, but too high a content will cause a high glass phase content, affecting the light transmittance and mechanical properties of the microcrystalline glass, and also affecting the transparency, so it should be controlled below 5%; the addition of MgO can further improve the uniformity, thermal stability and light transmittance of the microcrystalline glass system, but too much content can affect the chemical strengthening effect of the glass, resulting in difficulty in increasing the compressive stress layer during chemical strengthening treatment, and also affecting the crystal precipitation of the microcrystalline glass, so it is controlled below 5%. Although Na2O is not essential, it is a component that improves the fusibility of glass. When there is too much Na2O, lithium metasilicate crystals are not easy to precipitate or the chemical strengthening characteristics are reduced, so the content of Na2O is set to 0-5%. B2O3 acts as a flux, which can reduce the high-temperature viscosity of glass, improve the solubility of glass and the surface scratch resistance, but too high a content will lead to reduced hydrolysis resistance and chemical durability of microcrystalline glass, so it is controlled within 5%.

[0030] Li2O, Na2O and K2O are introduced in the form of carbonates or nitrates, P2O5 is introduced in the form of aluminum metaphosphate and diammonium phosphate, and the remaining raw material components are introduced in the form of oxides. This can simplify the production process and improve production efficiency.

[0031] The present invention also provides a method for preparing the lithium metasilicate glass-ceramics as described above, wherein the raw material components are mixed in proportion and heated to melt into glass liquid; the glass liquid is cast to obtain a base glass; the base glass is annealed and sliced ​​to obtain a sheet-like base glass; the sheet-like base glass is subjected to nucleation and crystallization heat treatment; after the crystallization heat treatment, the sheet-like base glass is strengthened to obtain a lithium metasilicate glass-ceramics. The prepared glass-ceramics is mainly composed of lithium metasilicate and a small amount of lithium disilicate phase, which can significantly improve the mechanical strength and transparency of the glass-ceramics, and can better meet the needs of cover glass. The method is simple, does not require the modification of existing equipment, and is suitable for industrialization. The lithium metasilicate glass-ceramics prepared by the above preparation method has a crystallinity of more than 60%, and contains 30% to 60% of lithium metasilicate crystal phase by weight; and the lithium metasilicate crystal phase occupies a higher percentage of the raw material than the other crystal phases. When the thickness is 1mm, the light transmittance of wavelength 400nm-1000nm is greater than 85%, and the haze is ≤0.3%; the blue light blocking rate of wavelength 400nm~450nm is ≥27%; the fracture toughness is ≥1.0MPa·m 1 / 2 , grain size ≤60nm, Vickers hardness up to 800kgf / mm 2The elastic modulus can reach more than 100Gpa; the surface compressive stress can reach more than 400MPa; the depth of the ion exchange layer is ≥80μm; the simulated drop height of the whole machine is more than 1m. While retaining transparency, the microcrystalline glass has the characteristics of large surface compressive stress, high strength, strong ion exchange capacity, excellent impact resistance and drop resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention is a schematic diagram of a process for preparing lithium metasilicate glass-ceramics.

[0033] Figure 2 This is a DSC chart of the base glass of Example 3 of the present invention.

[0034] Figure 3 This is the XRD diagram of Example 3 of the present invention after crystallization and thermal treatment.

[0035] Figure 4 This is a transmittance diagram of a 1 mm thick sample after crystallization and strengthening treatment according to Example 3 of the present invention. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0037] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0038] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0039] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0040] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0042] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0043] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0044] The invention discloses a lithium metasilicate glass-ceramic, which comprises the following raw material components by mass percentage: 62%-78% of SiO2, 3%-10% of Al2O3, 4%-18% of Li2O, 0%-5% of K2O, 0.6%-7.5% of P2O5, 2%-15% of ZrO2, 0-5% of ZnO, 0-3% of SnO2, 0-5% of Na2O, 0-5% of MgO and 0-3% of B2O3, wherein the value of (SiO2+ / Al2O3)Li2O is 6-15, the value of Al2O3 / Li2O is 0.7-1.3, and P2O5+ZrO2 is less than 8%. The microcrystalline glass comprises 30% to 60% by weight of lithium metasilicate crystal phase, has a transmittance of ≥85% for wavelengths of 400 to 1000 nm and a haze of ≤0.3% under the condition of 1 mm thickness, and also comprises a small amount of lithium disilicate crystal phase.

[0045] The present invention also provides a method for preparing the lithium metasilicate glass-ceramics as described above, comprising:

[0046] S1: According to the designed proportion of glass oxide components, the corresponding raw materials are weighed and mixed, and heated and melted into glass liquid. Specifically, according to the mass percentage of oxides, 62% to 78% SiO2, 3% to 10% Al2O3, 4% to 18% Li2O, 0% to 5% K2O, 0.6% to 7.5% P2O5 and 2% to 15% ZrO2 are introduced for weighing and mixing, and heated and melted into glass liquid at 1500°C to 1600°C; wherein the value of (SiO2+)Al2O3 / Li2O is 6 to 15, the value of Al2O3 / Li2O is 0.7 to 1.3, and P2O5+ZrO2 is less than 8%; 0 to 5% ZnO, 0 to 3% SnO2, 0 to 5% Na2O, 0 to 5% MgO and 0 to 3% B2O3 can also be introduced.

[0047] S2: Casting the glass liquid to obtain basic glass, specifically:

[0048] The molten glass liquid is cooled to 600°C to 700°C and cast into a mold. After the casting is completed, the basic glass is obtained;

[0049] S3: annealing the base glass and slicing it to obtain sheet-shaped base glass, specifically:

[0050] The base glass is annealed at 400°C to 550°C for 1 to 4 hours and sliced ​​to obtain a sheet-like base glass;

[0051] S4: performing nucleation and crystallization heat treatment on the sheet-like base glass, specifically:

[0052] Preheat the crystallization furnace to 100°C, place the sheet-like base glass on the carbon silicon plate, place it in the crystallization furnace, heat it to 480°C~650°C at a heating rate of 1°C / min~20°C / min and keep it warm for 0.5~16h for nucleation treatment to produce a crystalline phase and a glass composition; heat it to 600°C~900°C at a heating rate of 1°C / min~20°C / min and keep it warm for 0.5~16h for crystallization treatment, then cool it to 300°C at a cooling rate of 1°C / min~20°C / min and cool it with the furnace to complete the crystallization thermal treatment.

[0053] S5: After the crystallization and thermal treatment, the sheet-like base glass is strengthened to obtain lithium metasilicate glass-ceramics, specifically:

[0054] The sheet-like base glass after crystallization and heat treatment is placed in molten salt and ion exchange is carried out at 420°C to 520°C for 0.5 to 16 hours. The molten salt for ion exchange is one or more of sodium nitrate, potassium nitrate, sodium carbonate and potassium carbonate, preferably a mixed molten salt of sodium nitrate and potassium nitrate. During the ion exchange process, the smaller alkali metal ions in the glass or glass-ceramic are replaced or "exchanged" by larger alkali metal ions with the same valence state close to the glass and / or glass-ceramic. The larger ions replace the smaller ions, and compressive stress is built in the glass or glass-ceramic to form a compressive stress layer.

[0055] The softening point of the prepared microcrystalline glass is 650℃~680℃, the strain point is 440℃~470℃, the temperature range corresponding to 1000P~10000P is 900℃~1200℃, and the viscosity-temperature characteristics of the precursor glass are suitable for various molding processes such as calendering, casting, and float.

[0056] The glass composition or glass-ceramics of the present invention can be manufactured into a sheet-like glass forming body by grinding or polishing, but the method of manufacturing the glass forming body is not limited to these methods. The size of the glass-ceramics products of the present invention is not limited, and the thickness of the glass-ceramics products is 0.5 to 1.2 mm. In some embodiments of the present invention, the base glass or glass-ceramics can be processed into sheets and / or shaped (such as punching, hot bending, etc.), polished and / or swept after shaping, and then chemically tempered by a chemical tempering process.

[0057] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided. The present invention embodiments have been tried to ensure the accuracy of the values ​​(such as quantity, temperature, etc.), but some errors and deviations must be taken into account. The composition itself is given in mass percentage based on oxides and has been standardized to 100%.

[0058] It should be noted that the various properties of the glass-ceramics and / or glass-ceramics products of the present invention are tested by the following methods:

[0059] Haze: A CS-700 haze tester was used, with 1 mm thick glass samples prepared and tested according to GB2410-80.

[0060] Expansion coefficient: The samples were processed into glass sheets of 50 mm*15 mm and tested using an Orton DIL 2010STD thermal expansion instrument.

[0061] Transmittance: The sample was processed into a thickness of 1 mm, and the average light transmittance in the range of 200 to 1000 nm was measured using a Hitachi U-41000 spectrophotometer.

[0062] Crystallinity: The XRD diffraction peaks are compared with the database spectrum. The crystallinity is obtained by calculating the proportion of the crystalline phase diffraction intensity in the overall spectrum intensity.

[0063] Elastic modulus: The samples are processed into standard test sample size, polished, and free of scratches, cracks, and chippings, and tested in accordance with GB37780-2019.

[0064] Fracture toughness: Fracture toughness is measured using methods known in the technical field. The present invention uses the Vickers hardness indentation method and is measured according to GB / T 37900-2019, "Ultra-thin glass hardness and fracture toughness test method small load Vickers indentation method".

[0065] Surface stress (CS): Surface stress was measured using a glass surface stress meter FSM-6000.

[0066] Depth of ion exchange layer (DOL): The depth of ion exchange layer was measured using a glass surface stress meter SLP-2000.

[0067] Machine drop: At room temperature, the strengthened microcrystalline glass is processed into a glass sheet of 144*66*0.7mm, and the long and short margins are respectively 1mm. It is pasted on the steel sheet of 146*68*1mm with UV glue. The glass surface is vertically dropped toward the horizontal marble floor covered with 80-mesh sandpaper by a drop tester. The height starts from 200cm and the interval is 100cm until a through crack appears on the sample. The height of the through crack is recorded. Each sample is tested 5 times, and the average height is recorded as the drop height.

[0068] Liquidus Temperature: The temperature at which the first crystal is observed in a standard gradient boat liquidus measurement (ASTM C829-81 and later versions). The liquidus viscosity is determined from the liquidus temperature and the coefficients of the Fulcher equation and is given in poise.

[0069] Specific embodiments and related performance test results are shown in the following table:

[0070]

[0071]

[0072]

[0073] It can be seen that the microcrystalline glass prepared by the present invention not only has large surface compressive stress, high strength, strong ion exchange capacity, excellent impact resistance and drop resistance, but also has better transparency.

[0074] Figure 2This is the DSC graph of the base glass of Example 3. The base glass of Example 3 was heated to 1000°C in argon at a rate of 10°C / min. It can be seen that the glass transition temperature is 512.5°C, and the temperatures of the two crystallization exothermic peaks are 646.6°C and 807.1°C. The former can be used as a reference temperature point for nucleation treatment, while the latter can be used as a reference temperature point for crystallization treatment.

[0075] Figure 3 This is the XRD diagram of Example 3 after the crystallization and heat treatment, which shows that the crystallized glass contains lithium metasilicate and lithium silicate (lithium disilicate).

[0076] Figure 4 This is the transmittance diagram of the 1 mm thick sample after crystallization and strengthening treatment in Example 3. It can be seen that the transmittance in the wavelength range of 400nm to 1000nm is greater than 85%, and the microcrystalline glass is transparent in the visible light range (400nm to 800nm).

[0077] The lithium metasilicate glass-ceramics prepared by the preparation method has a crystallinity of more than 60%, contains 30% to 60% by weight of lithium metasilicate crystal phase; when the thickness is 1 mm, the light transmittance of the wavelength of 400nm to 1000nm is greater than 85%, and the haze is ≤0.3%; the blue light blocking rate of the wavelength of 400nm to 450nm is ≥27%; the fracture toughness is ≥1.0MPa·m 1 / 2 , grain size ≤60nm, Vickers hardness up to 800kgf / mm 2 , elastic modulus can reach 100Gpach; surface compressive stress can reach more than 400MPa; ion exchange layer depth ≥ 80μm; its simulated whole machine drop height is more than 1m. This microcrystalline glass retains transparency while having the characteristics of large surface compressive stress, high strength, strong ion exchange capacity, excellent impact resistance and drop resistance.

[0078] In summary, the present invention provides a lithium metasilicate glass-ceramic and a preparation method thereof. By regulating the glass-ceramic components and the preparation method, the glass-ceramic can have better mechanical strength while maintaining high transparency, which meets the development requirements in the field of electronic device protective glass.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A lithium metasilicate glass-ceramic, characterized in that: Calculated by oxide mass percentage, it comprises: 62% to 78% SiO2, 3% to 10% Al2O3, 4% to 18% Li2O, 0% to 5% K2O, 0.6% to 7.5% P2O5 and 2% to 15% ZrO2, the value of (SiO2+)Al2O3 / Li2O is 6 to 15, the value of Al2O3 / Li2O is 0.7 to 1.3, and P2O5+ZrO2 is less than 8%; The microcrystalline glass includes 30% to 60% by weight of lithium metasilicate crystal phase.

2. The lithium metasilicate glass-ceramics according to claim 1, characterized in that: The microcrystalline glass has a transmittance of 85% or more at a wavelength of 400 to 1000 nm and a haze of 0.3% or less under the condition of a thickness of 1 mm.

3. The lithium metasilicate glass-ceramics according to claim 1, characterized in that: It also includes 0-5% ZnO, 0-3% SnO2, 0-5% Na2O, 0-5% MgO and 0-3% B2O3.

4. The lithium metasilicate glass-ceramics according to claim 1, characterized in that: The glass-ceramics also includes a lithium disilicate crystal phase.

5. The lithium metasilicate glass-ceramics according to claim 1, characterized in that: Its Vickers hardness is greater than 800kgf / mm 2 , elastic modulus is greater than 100Gpa.

6. The lithium metasilicate glass-ceramics according to claim 1, characterized in that: Its fracture toughness ≥1.0MPa·m 1 / 2 .

7. The lithium metasilicate glass-ceramics according to any one of claims 1 to 6, characterized in that: After chemical strengthening, the surface compressive stress is greater than 400 MPa, and the depth of the ion exchange layer is greater than or equal to 80 μm.

8. A method for preparing lithium metasilicate glass-ceramics, characterized in that: include: In terms of oxide mass percentage, 62% to 78% SiO2, 3% to 10% Al2O3, 4% to 18% Li2O, 0% to 5% K2O, 0.6% to 7.5% P2O5 and 2% to 15% ZrO2 are introduced for weighing and mixing, and heated and melted into glass liquid; wherein the value of (SiO2+)Al2O3 / Li2O is 6 to 15, the value of Al2O3 / Li2O is 0.7 to 1.3, and P2O5+ZrO2 is less than 8%; Casting the glass liquid to obtain basic glass; The base glass is annealed and sliced ​​to obtain sheet-shaped base glass; The sheet-like base glass is subjected to a nucleation and crystallization heat treatment; After the crystallization and heat treatment is completed, the sheet-like base glass is chemically strengthened to obtain lithium metasilicate microcrystalline glass.

9. The method for preparing lithium metasilicate glass-ceramics according to claim 8, characterized in that: The heating and melting temperature is 1500°C to 1600°C.

10. The method for preparing lithium metasilicate glass-ceramics according to claim 8, characterized in that: The temperature of the base glass annealing treatment is 400°C to 550°C, and the annealing time is 1 to 4 hours.

11. The method for preparing lithium metasilicate glass-ceramics according to claim 8, characterized in that: The method of heat treating the sheet-like base glass for nucleation and crystallization is as follows: After annealing, the steel is heated to 480°C to 650°C for nucleation treatment; After the nucleation treatment, the temperature is heated to 600°C to 900°C for crystallization treatment, and the furnace is cooled to complete the nucleation and crystallization thermal treatment.

12. The method for preparing lithium metasilicate glass-ceramics according to claim 8, characterized in that: The heating rate for the nucleation treatment and the crystallization heat treatment is 1°C / min to 20°C / min; the time for the nucleation treatment and the crystallization heat treatment is 0.5 to 16 hours.

13. The method for preparing lithium metasilicate glass-ceramics according to claim 8, characterized in that: The glass-ceramics after crystallization and thermal treatment are chemically strengthened. The molten salt used for chemical strengthening is one or more of sodium nitrate, potassium nitrate, sodium carbonate and potassium carbonate. The strengthening temperature is 420° C. to 520° C. and the strengthening time is 0.5 to 16 hours.

Citation Information

Patent Citations

  • Microcrystalline glass and substrate thereof

    CN107902909A

  • Glass ceramic, glass ceramic precursor and preparation method thereof

    CN115893849A

  • Transparent microcrystalline glass as well as preparation method and application thereof

    CN116102260A

Cited By

  • High-crystallinity transparent lithium aluminosilicate glass-ceramic and preparation method therefor

    WO2026129423A1